Building Capacity for Behavioral Health Services and Clinical Research in a Rural Primary Care Clinic: A Case Study - Laura M. Daniels; Kim E. Dixon; Lisa C. Campbell (AIMS Press, 2014)
Integrating sustainable, evidence-based, and collaborative depression screening and follow-up treatment into primary care clinics is a significant challenge in health care. In this article a case study approach is used to describe the process of building capacity for a depression screening program in a rural federally qualified health center (FQHC). A conceptual framework addressing the clinical, operational, and financial perspectives of a primary care setting is applied restrospectively to identify 1) the barriers and facilitating factors associated with integrating a depression screening program into standard practice and 2) how the program was leveraged to conduct clinical research to improve self-management in patients with diabetes and elevated depressive symptoms.